Toussaint Louverture A Black Jacobin in the Age of Revolutions - Forsdick, Charles (Revolutionary Lives, 2017)
Toussaint Louverture (c1743-1803) was the heroic leading figure in the Haitian Revolution of 1791-1804, the only successful slave revolt in recorded history, and he remains an international inspiration, seen by many to be one of the greatest anti-imperialist fighters who ever lived. Toussaint was a military genius who led an army composed overwhelmingly of former enslaved Africans and people of African descent to victory after victory under the banner 'Liberty or Death' over the professional armies of France, Spain and Britain, before paying the ultimate price himself for refusing to compromise with imperial power at the expense of the maintenance of liberty for all. This new political biography of Toussaint aims to provide readers with an accessible yet scholarly introduction to his complex life while critically analysing Toussaint's political thought, his contribution as a revolutionary leader, and his legacy for both Haiti and the wider world.